FOSTERING CULTURALLY DIVERSE LEADERSHIP IN ORGANISATIONS - Loon, Karen, 1969- author. ([S.l.])
1 online resource
Keywords: Leveraging academic research and case studies, knowledge as a business leader and diversity practitioner, and personal experience, Karen Loon examines how successful culturally diverse leaders at work resolve the contradictions and tensions of their identities within organisations. What can we learn from those leaders who have thrived and smashed the bamboo ceiling'? Moreover, are there other factors holding organisational change back? The book proposes research-based recommendations for aspiring leaders and corporate practitioners whilst revealing the potential inhibitors to progress. Split into three sections, Loon examines current research on identities in multicultural nations and organisations, delves into the career progression of successful Asian-Australian leaders to explore how they negotiate identity in the workplace, and provides a roadmap of actions for business leaders looking to create more inclusive and diverse cultures in their organisations. Written for both people new to diversity and those keen on new perspectives, the book is well-suited for aspiring leaders at any stage of their careers looking to accelerate their careers, as well as C-Suite, HR, and Diversity leads.